1968
DOI: 10.1063/1.1656788
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Mechanism of Rebinder Effects in CaF2

Abstract: A study has been made of the influence of adsorbed species on the room-temperature mobility of near-surface dislocations introduced into freshly cleaved {111} CaF2 surfaces by a diamond indenter. It was found that, in general, adsorbed surface-active ions or molecules decrease dislocation mobility, i.e., increase microhardness. Studies of the relaxation behavior of near-surface dislocations in CaF2 exposed to solutions of DMF in DMSO revealed that these environments also can influence dislocation mobility in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

1970
1970
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…Indeed, generally speaking, the "Rehbinder effect" [Rehbinder and Lichtman, 1957], due to the reduction of the surface energy of different kinds of walls (e.g., pores, flaw, microfissure) by the adsorbed water, promotes the propagation of these walls if the deviatoric stress is high enough. In addition, Westwood and Goldheim [1968] suggested that the adsorbance of a polar fluid onto the crystal surface modifies the interactive behavior of point and line (dislocations) defects which largely determine the mobility of dislocations during the plastic deformation of ionic crystals, such as calcite. Hence, even though our experimental conditions (T = 70°C; Pc = 15-20 MPa) do not favor intracrystalline plastic deformation in calcite [Rutter, 1983;De Bresser et al, 2002;Zhang and Spiers, 2005b], the contribution of intracrystalline viscoplasticity to the creep of our wet (Pi = 10 MPa) limestone sample ( Figure 12) may not be negligible.…”
Section: Viscoplasticitymentioning
confidence: 99%
“…Indeed, generally speaking, the "Rehbinder effect" [Rehbinder and Lichtman, 1957], due to the reduction of the surface energy of different kinds of walls (e.g., pores, flaw, microfissure) by the adsorbed water, promotes the propagation of these walls if the deviatoric stress is high enough. In addition, Westwood and Goldheim [1968] suggested that the adsorbance of a polar fluid onto the crystal surface modifies the interactive behavior of point and line (dislocations) defects which largely determine the mobility of dislocations during the plastic deformation of ionic crystals, such as calcite. Hence, even though our experimental conditions (T = 70°C; Pc = 15-20 MPa) do not favor intracrystalline plastic deformation in calcite [Rutter, 1983;De Bresser et al, 2002;Zhang and Spiers, 2005b], the contribution of intracrystalline viscoplasticity to the creep of our wet (Pi = 10 MPa) limestone sample ( Figure 12) may not be negligible.…”
Section: Viscoplasticitymentioning
confidence: 99%
“…Rehbinder & Lichtman (1957) attributed the weakening of single crystals by the action of water to a reduction of interfacial tension and suggested that this reduces the work hardening component due to the pile-up of dislocations at the crystal-fluid interface, and increases the probability of emergence of dislocations onto the crystal surface. Westwood & Goldheim (1968) have suggested that the adsorbance of a polar fluid onto the crystal surface modify the interactive behaviour of point and line (dislocations) defects which largely determine the mobility of dislocations during the plastic deformation of ionic crystals, such as calcite. They also suggested that this is not a surface effect, like the alteration of the surface energy of the crystal, but one which penetrates up to 10 μm into the crystal.…”
Section: The Physio-chemical Effects Of Watermentioning
confidence: 99%
“…: After the completion of microhardness measurements the specimens were etched with a 0.7 n solution of HNO, to reveal dislocation etch pits and the distribution of dislocations around the indentation. The characteristic features of such dislocation patterns or rosettes in CaF, have been described earlier by Westwood and Goldheim [15]. The length of the arms of such rosette patterns on the { 111} planes of CaF, is proportional to the mobility of edge dislocations.…”
Section: Methodsmentioning
confidence: 59%